2010
DOI: 10.1590/s1516-35982010000400020
|View full text |Cite
|
Sign up to set email alerts
|

Anual variation of morphologic traits and hair coat surface temperature of Holstein cows in semi-arid environment

Abstract: RESUMO -O objetivo neste trabalho foi estudar a variação anual da temperatura superficial e outras características do pelame de vacas holandesas em ambiente tropical, considerando separadamente as malhas negras e brancas. Foram medidas as características espessura da capa (mm), comprimento dos pelos (mm), número de pelos (pelos/cm 2 ) e temperatura da superfície do pelame em 191 vacas mestiças com alta proporção de sangue holandês (7/8 e 31/32, respectivamente), distribuídas em três rebanhos em ambiente semiár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…The recorded values were similar to those reported in Holstein cows in winter (2.88 mm; Mata and Silva et al, 2013) and higher than those recorded in crossbred dairy cows in a semiarid region (1.93 mm; Façanha et al, 2010). These authors reported higher hair coat thickness values in animals harboring high proportions of Holstein genes than in animals derived from crossbreeding with Guzera cows, which are more adapted to tropical environments and, thus, exhibit a thinner coat with short, wellsettled hairs, which contributes to a greater loss of heat energy.…”
Section: Resultssupporting
confidence: 87%
“…The recorded values were similar to those reported in Holstein cows in winter (2.88 mm; Mata and Silva et al, 2013) and higher than those recorded in crossbred dairy cows in a semiarid region (1.93 mm; Façanha et al, 2010). These authors reported higher hair coat thickness values in animals harboring high proportions of Holstein genes than in animals derived from crossbreeding with Guzera cows, which are more adapted to tropical environments and, thus, exhibit a thinner coat with short, wellsettled hairs, which contributes to a greater loss of heat energy.…”
Section: Resultssupporting
confidence: 87%
“…This variable is prone to variations, since it is associated with the environment, climatic changes, and physiological changes such as vascularization and perspiration (FERREIRA et al, 2006). Façanha et al (2010) submit that the hair-coat color influences the body temperature due to the greater heat absorption. In the present study, all animals had a black epidermis.…”
Section: Resultsmentioning
confidence: 99%
“…Several coat characteristics are preferable for cows in tropical climates, such as short, high-density coats, high diameter, and light-colored hair with an inclination less than 40 • , and pigmented skin [38,39]. These characteristics allow more protection from solar radiation and heat stress, contributing to animal comfort and better production under field conditions [40].…”
Section: Morphological Characteristics Of Skin Coat and Body Measures Of Cows In Shaded Iclf And Full Sun Systemsmentioning
confidence: 99%